Pauling entropy, metastability, and equilibrium in Dy2Ti2O7 spin ice - Giblin, SR; Twengström, M; Bovo, L; Ruminy, M; Bartkowiak, M; Manuel, P; Andresen, JC; Prabhakaran, D; Balakrishnan, G; Pomjakushina, E; Paulsen, C; Lhotel, E; et al. (American Physical Society, 2018)
Determining the fate of the Pauling entropy in the classical spin ice material Dy2Ti2O7 with respect to the third law of thermodynamics has become an important test case for understanding the existence and stability of ice-rule states in general. The standard model of spin ice—the dipolar spin ice model—predicts an ordering transition at T≈0.15  K, but recent experiments by Pomaranski et al. suggest an entropy recovery over long timescales at temperatures as high as 0.5 K, much too high to be compatible with the theory. Using neutron scattering and specific heat measurements at low temperatures and with long timescales (0.35  K/106  s and 0.5  K/105  s, respectively) on several isotopically enriched samples, we find no evidence of a reduction of ice-rule correlations or spin entropy. High-resolution simulations of the neutron structure factor show that the spin correlations remain well described by the dipolar spin ice model at all temperatures. Furthermore, by careful consideration of hyperfine contributions, we conclude that the original entropy measurements of Ramirez et al. are, after all, essentially correct: The short-time relaxation method used in that study gives a reasonably accurate estimate of the equilibrium spin ice entropy due to a cancellation of contributions.